Surakarta Indies Style Architecture for Cold Night Batik Design on Adult Women's Clothing - Ivana Claresta; Darwoto (Hastagina : Jurnal Kriya Seni, 2023)
This design was carried out as a forum for education and insight for the general public as well as mobilizing the community to create a sense of awareness of the importance of maintaining Indische-style government buildings in Surakarta which are cultural heritage. The method used consists of design methods, design concepts, and visualization. The design method uses Collin Clipson's theory which goes through the stages of Problem Analysis, Data Collection, Testing, and determining the initial design idea. The design concept includes the rationale for textile design. Visualization is the stage of visualizing the concept of the design plan.The results of this design are as follows: (1) Visual architectural style of Indis Surakarta for the design of contemporary batik designs. (2) The application of this design is directed at clothing for adult women with an age range of 25-30 years, taking into account the selection of appropriate colors and compositions so as to produce products that are innovative, creative, and have characteristics and updates in terms of design.